OCCURRENCE, GEOCHEMISTRY AND INDUSTRIAL QUALITY OF NAFADA GYPSYM DEPOSIT, NORTHEASTERN NIGERIA - R.P, TABALE; E. E, NTEKIM; A, OLASEHINDE; Y, ABUBAKAR (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
Three varieties of gypsum deposits occur in numerous locations within the Senonian Fika Shale in Nafada area, northeastern Nigeria. Geological investigations at Gonja, Warum, Ganko, Shole, Sudingo, Gadi, Mada and Papa mines show the occurrence of the three varieties namely: Satinspar, Selenite and Alabaster. These gypsum deposits occur within the gypsiferous Fika Shale with thicknesses within the span of 1 to 6 cm and depth of 0.2 to 15 meters. The gypsum are hosted within veins sometimes criss - crossing in some locations, pores and fractures inter layered within the fissile Fika Shale intercalated with mud. Analyses of seventeen fresh gypsum samples by X-ray spectrophotometer technique indicate mean average compositions of 93.06, 92.59 and 93.60 wt % of CaSO4.2H2O; 2.04, 2.32 and 1.80 wt % SiO2; 0.38, 0.40, and 0.70 wt % of Fe2O3+AL2O3; 0.36, 0.34 and 0.11 wt % of MgO; 0.13, 0.14 and 0.13 wt of Alkalis (Na2O +K2O) and purity of 96.43, 96.48 and 96.42 for Satinspar, Selenite and Alabaster respectively. These chemical data indicate high grade of gypsum which may be suitable in: cement, ammonium sulphate fertilizer, pharmaceutical, ceramics/pottery, cosmetics, soil amendment, building, chemical, paints and textile industries.